Tissue culture of European accessions of persimmon: Callusing and proliferation - Giordani E.; Perria R.; Bellini E. (First Mediterranean symposium on persimmon, 2002)
The suitability to tissue culture and the callusing activity was assessed on European varieties (namely 'Cioccolatino', 'Mercatelli', 'Moro', 'Rispoli' within the Italian germplasm, and 'Betera 1', 'Enguera 1', 'La Selva', 'Reus 15', 'Rojo Brillante', 'Tomatero', 'Xato del Bon Repos' and 'Picudo', among the Spanish varieties) in comparison to Japanese cultivars ('Jiro' and 'Tone Wase') and to 'Kaki Tipo'. Explants from dormant buds were cultured in MS basal medium, with 20 g per l of sucrose, solidified with ICN - Gel Gro (Gellum gum), added with Zeatin, Indole-3-Acetic Acid. After 60 days of culture in the dark at 23 degrees C calluses were measured and weighted. The best results were obtained on 'Tone Wase', 'Tomatero', 'Reus 15', 'Rojo Brillante', 'Xato del Bon Repos', 'La Selva' and 'Picudo', with very active white calluses. The suitability to micropropagation of 'Rojo Brillante', a very important PCA cultivar in the Spanish persimmon industry, was assessed.
1. Mediterranean Symposium on Persimmon, 2001/11/23-24, Faenza (Italy)